The Francisco Arcellana Library a case study of the conservation practices on the videotape collection - Lopez, Clarisse T. (2002)
The Francisco Arcellana Library caters to the courses in Communication, Arts and Literature of the Department of English and Comparative Literature, under the College of Arts and Letters in the University of the Philippines Diliman. The Library videotapes provide film viewings for a holistic view of the lessons discussed in the classroom. Due to frequent use, the materials, in turn, become susceptible to immediate deterioration. Videotapes are delicate materials bearing information and, if not properly maintained, their physical condition could easily be corrupted. What does the Library do to help prolong the use of the videotapes?